The territorial exchange between Poland and the USSR in 1951: demographic development and settlement network transformation over a 70-year period - Lozynskyy, Roman; Slyvka, Roman; Pantyley, Viktoriya; Braychevskyy , Yulian (Bulletin of Geography. Socio-economic Series, 2023)
In this article, we present a comparative analysis of the demographic development and changes in the settlement network over the last 70 years in the territories exchanged in 1951 between the USSR and Poland. We found that, within the territory ceded to the USSR, the traditional settlement pattern was restored and the settlement network was renewed up to 90%. Industrialization in the area resulted in the population growth reaching, at maximum, 40% greater numbers than in 1939. The territory ceded to Poland featured a “colonizational” pattern of resettlement and the population size remained much smaller as compared to 1951, directly before the exchange. However, in Poland, local people faced no obstacles to returning to the area. Conversely, the USSR deported most of the local inhabitants to distant parts of Ukraine and prevented people from the neighbouring locations from entering the area. Overall, based on the resettlement policy comparison we argue that, on the part of the USSR, an important rationale behind the exchange was to strengthen totalitarian control over the western regions of Ukraine by means of deportation and population dispersion